RECKLINGHAUSEN'S DISEASE IN А PREGNANT WOMAN: A CLINICAL CASE - Владимир Кириллович Чайка; Ирина Тихоновна Говоруха; Виталина Васильевна Вустенко; Арина Александровна Земелько (Мать и дитя в Кузбассе, 2025)
Recklinghausen's disease (neurofibromatosis) was first described in 1882. Neurofibromatosis (non-malignant) is classified as a phacomatosis according to the International Classification of Diseases X revision (Q85.0) and is included in the list of orphan diseases. Diagnostic criteria for neurofibromatoses were developed by the US National Institutes of Health (NIH) in 1987 and clarified by international consensus in 2021. Neurofibromatosis type I is a hereditary disease affecting 50% of offspring. The article describes a clinical case of neurofibromatosis in a pregnant woman with a family history of Recklinghausen's disease with the birth of a healthy child.